Islamic Da'wah and Cancel Culture on Virtual Media (A Case of Salafi in Lombok) - Nazar Naamy (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This article aims to examine the cancel culture phenomenon experienced by a speaker Tuan Guru Mizan Qudsiyah from Lombok NTB on YouTube in 2020. The questions in this article are what is cancel culture, how does cancel culture impact individuals and groups, how does Islamic communication view the cancel culture phenomenon, how are the implications of cancel culture on Tuan Guru Mizan Qudsiyah. This research uses qualitative methods with a case study approach and this research data is taken from YouTube and then analyzed using Pierre Bourdieu's genetic structuralism theory. The results of this study revealed that cancel culture is rejection, cancellation, and boycott carried out by netizens to eliminate the charisma of a public figure because of controversial words and actions on virtual media. Individually, cancel culture results in anxiety, stress, depression, and loss of privacy. While in groups can cause social fears that are not in accordance with the norm which eventually experience restrictions on expression. Islamic communication views the phenomenon of cancel culture in virtual media as a new parasite in carrying out the principles of Islamic communication such as justice, forgiveness, dialogue, deliberation, providing opportunities for self-improvement, compassion, empathy, tenderness, and respecting differences. As for the implications of cancel culture against Tuan Guru Mizan Qudsiyah from East Lombok on YouTube in 2020 for his statement insulting the tombs of Lombok guardians as "Sasak Language: Makam Tain Acong and Tain Acong Keramat: Dog Feces Grave and Dog Feces Sacred "which in the end he was canceled by the mob and then his Assunah Islamic boarding school in Bagek Nyaka, Aikmel District, East Lombok Regency, West Nusa Tenggara was attacked and burned.